Web Series Dalam Format Film Pendek Tentang Dampak Kecanduan Game Online Terhadap Perilaku Remaja Sebagai Media Kampanye Sosial (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2021)
Web Series is one of the shows found on YouTube and other social media. The concept of a Web Series is similar to a television show, but the duration of the broadcast is shorter, around 5-15 minutes. Not inferior to feature films, the Web Series also has many fans because it is easy to access, only uses gadgets and an internet connection, therefore, Web series can be one of the media for social campaigns, one of which is a campaign about the impact of online game addiction on adolescent behavior.. This work is a Web Series that tells about some students who are addicted to playing online games. This changes their behavior, and forms a personality to be indifferent, say rude, disrespectful to parents, lazy to study and so on. Of course, this Web Series has a message stored in it so that the purpose of campaigning in a Web Series is accomplished.